Proposta de um sistema de gerência de redes PLC utilizando SNMPv3 - OLIVEIRA, Diogo Nunes de (2009)
ACCESS technologies for data transmission, such as xDSL, Wi-¯ and cable modem are widely used because they support high data transmission rates at low cost. Among these technologies, Power Line Communications, known as PLC, is a promising solution. PLC technology transmits data over power network, which presents high capilarity, due to the fact that it is present in 99% of residences. Since most of its structure already exists, power supply concessionaries started investing in this solution to stop being only a power supply concessionary and to be also a telecommunication company. In order to obtain control over a technology it is necessary to use management techniques that permits the maximum extraction of information from technology and involved devices. One of the goals of this work is to present the management solution developed to PLC networks. This solution di®ers from network management solutions used on other data transmission technologies due to the transmission media utilized. The management software used as base of the management system implemented is a free and no cost software. The concept of free code was adopted to the solutions implemented to the management system. The other goal of this work is to present the proposal and implementation of an embedded system based on PIC microcontroller that performs conversion of versions of SNMP protocol, which is the default management protcol in TCP/IP based networks. This converter device brings security to PLC networks management, since PLC devices only support version 2c of SNMP protocol, which is faulty regarding security. Since SNMPv3 supports authentication and privacy al gorithms, the designed converter device is capable of providing security, due to its capacity of coding a SNMPv2c packet into a SNMPv3 packet, and vice-versa.